ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN DAERAH DALAM MENDUKUNG OTONOMISASI DAERAH DI PEMERINTAH KOTA AMBON - Charlota Jeany Titahena (Soso-Q : Jurnal Manajemen, 2019)
This study aims to analyze and find out the Financial Performance of BPKAD Ambon City during the period 2007-2018 and to determine the extent of the Regional Government's Financial Performance through the Level of Effectiveness, Dependency, Fiscal Decentralization Degree, Level of Independence of Ambon City Regional Government in implementing Regional Autonomy. This research was conducted at the Ambon City Regional Financial and Asset Management Agency using Secondary Data, the Ambon City Government's Financial Realization Report published in 2007-2018.The analysis technique used is Path Analysis which is a development technique of Multiple Linear Regression. The results showed that the effectiveness ratio of PAD realization achieved by BPKAD was effective and very good, the overall dependency ratio was still very high for the central government, the degree of fiscal decentralization was still very poor and the ratio of independence was very low, this showed that the role of the Ambon City Government in the financing process Regional Finance is still the mainstay of the Central Government, from this it shows that in running the decentralized system the Ambon City Government has not been fully able to use PAD as a major factor in regional financing. Keywords: Effectiveness Ratio, Dependency Ratio, Degree of Fiscal Decentralization, Ratio of Independence of Regional Financial Performance as well as the success of Regional Autonomy.